1997
DOI: 10.1126/science.276.5311.394
|View full text |Cite
|
Sign up to set email alerts
|

Primary Production in Antarctic Sea Ice

Abstract: A numerical model shows that in Antarctic sea ice, increased flooding in regions with thick snow cover enhances primary production in the infiltration (surface) layer. Productivity in the freeboard (sea level) layer is also determined by sea ice porosity, which varies with temperature. Spatial and temporal variation in snow thickness and the proportion of first-year ice thus determine regional differences in sea ice primary production. Model results show that of the 40 teragrams of carbon produced annually in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
195
0

Year Published

2003
2003
2015
2015

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 227 publications
(200 citation statements)
references
References 5 publications
5
195
0
Order By: Relevance
“…A possible mechanism for the production of I 2 in the polar regions is the activity of ice algae and phytoplankton that produce iodine compounds, which are then wicked to the surface through brine channels (Mahajan et al, 2010). It has also been suggested that the primary productivity in Antarctic ice and waters may be higher than in the Arctic (Arrigo et al, 1997;Gosselin et al, 1997;Lizotte, 2001;Mahajan et al, 2010), possibly accounting for the difference in apparent iodine activity between the two poles. However, as the ice in the Arctic continues to thin, and as more multiyear ice has been replaced by seasonal sea ice (Nghiem et al, 2012), the algae and phytoplankton productivity in the Arctic has increased (Arrigo et al, 2008(Arrigo et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…A possible mechanism for the production of I 2 in the polar regions is the activity of ice algae and phytoplankton that produce iodine compounds, which are then wicked to the surface through brine channels (Mahajan et al, 2010). It has also been suggested that the primary productivity in Antarctic ice and waters may be higher than in the Arctic (Arrigo et al, 1997;Gosselin et al, 1997;Lizotte, 2001;Mahajan et al, 2010), possibly accounting for the difference in apparent iodine activity between the two poles. However, as the ice in the Arctic continues to thin, and as more multiyear ice has been replaced by seasonal sea ice (Nghiem et al, 2012), the algae and phytoplankton productivity in the Arctic has increased (Arrigo et al, 2008(Arrigo et al, , 2012.…”
Section: Discussionmentioning
confidence: 99%
“…First, the nutrient fluxes are based on simple formulations and do not account for brine transport. Consequently, the location of ice algal growth has to be prescribed, either at the base [e.g., Lavoie et al, 2005] or at the top of the ice cover [e.g., Arrigo et al, 1997;Saenz and Arrigo, 2012], and therefore the models are not general enough to handle both Arctic and Antarctic situations. Vancoppenolle et al [2010] and Jeffery et al [2011], have developed schemes to couple dissolved tracers to brine dynamics, and applied their model to successful simulations of silicate concentrations and salinity, respectively, but their approach has not yet been coupled to formulations of ecodynamics.…”
Section: Modelling and Up-scaling The Role Of Sea Ice In The Marine Bmentioning
confidence: 99%
“…The fraction of sea ice versus pelagic productivity is ~10% on average but is larger in the Arctic Basin, and smaller in the seasonally ice covered seas [Deal et al, 2011]. In the Antarctic, 1795 Tg C y -1 are produced in the open ocean, 114 Tg C y -1 are produced in the marginal ice zones, and from 40 to 70 Tg C y -1 are produced within the sea ice, based on observations of Chl a and modelling studies, respectively [Legendre et al, 1992;Arrigo et al, 1997]. Under-ice production is absent from those estimates, because those regions are beyond the reach of satellites.…”
Section: Light Transmissionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Antarctic is among the most isolated and dynamic regions on Earth, because of the Antarctic circumpolar current, coupled with massive and seasonally variable sea-ice cover (Arrigo et al, 1997;Arrigo and Thomas, 2004;Arrigo, 2014). The Southern Ocean plays a disproportionately large role in the regulation of Earth's climate and biogeochemical cycles (Boyd, 2002).…”
Section: Introductionmentioning
confidence: 99%